Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean - Fraser, Thomas H.; Randall, John E. (Zootaxa, 2003)
Apogon brevispinis is described from two specimens, the larger of which is missing the caudal peduncle, collected at the Austral Islands. This species has a tiny first dorsal-fin spine (5-8% of the third dorsal-fin spine length), 18-19 well-developed gill rakers on first arch, 5 predorsal scales, elongated last soft dorsal and anal fin-rays, 14 circumpeduncular scales, 5 broad tan-brown stripes alternating with 5 narrow whitish stripes, and an irregular dark caudal peduncle mark. Apogon regula is described from five specimens collected in Guam and the Carolina Islands. This species has a longer first dorsal-fin spine (10-15% of the third dorsal-fin spine length), 13-14 well-developed gill rakers on first arch, 4 predorsal scales, 12-13 circumpeduncular scales 5 broad golden-brown stripes alternating with 4 narrow whitish stripes, and dark brown broad stripes on the upper and lower caudal peduncle.